Development of Telegram Bot for Flipped Learning Chemistry Class with UCD Approach - Rizdania; Muniroh, Amirotul (Journal of Information Technology and Computer Science, 2021)
The need for media that supports online learning is increasing along with the Covid-19 pandemic that is spreading in the world. The learning media is expected to be in the form of media that is easy to use and does not require additional costs incurred by students. One application that is widely used today is Telegram. The application provides a telegram bot facility that can assist teachers in delivering the material they are taught. By using the telegram bot, students can easily use applications on their mobile phones without installing additional applications. This study discusses the development of online learning methods using telegram bots as a medium for delivering material to students using the approach of UCD. This study used usability testing to evaluate the Telegram bot as the media for flipped learning. There are five indicators measured in the usability evaluation we used in this research. The result of the assesment is 83.56%.